Cutaneous angiosarcoma of head and neck: Case report and literature review - Juliana Maria Rodrigues Sarmento Pinheiro; Tiago Novaes Pinheiro; Lidiane de Paula Ribeiro; Renato Oliveira Martins (Oral Oncology Reports)
Angiosarcomas are rare and aggressive malignant tumors of endothelial cells, they have a vascular or lymphatic origin. Diagnostic evaluation includes a biopsy to confirm the histopathological diagnosis, in addition to magnetic resonance imaging to delineate the extent of the primary lesion before surgery. We report an unusual clinical event of well-differentiated angiosarcoma in the nasogingival labial region in a female patient, 85-years-old, who sought care with increased sensitivity in the upper lip with progressive worsening and the appearance of pain and local edema. After a biopsy and immunohistochemical study, she was diagnosed with well-differentiated nasogingivolabial angiosarcoma. The patient underwent extensive surgical resection of the lesion with nasal amputation, resection of the upper lip, and partial palatectomy associated with postoperative radiotherapy. Then, she was referred to the oral and maxillofacial prosthesis service for rehabilitation. The patient was diagnosed with advanced stage metastasis in the liver 25 months after the surgical treatment, being under palliative care. Eight months later, the patient died. We also present a discussion of clinical and histopathological aspects, differential diagnosis and treatment modalities, In addition to a brief review of the literature on the subject.